1981
DOI: 10.1139/p81-054
|View full text |Cite
|
Sign up to set email alerts
|

The electronic emission spectrum of triatomic hydrogen. III. Infrared perpendicular bands near 3600 cm−1

Abstract: The experimental techniques for obtaining spectra of triatomic hydrogen are described with special reference to studies in the infrared. An electronic transition near 3600 cm−1 is observed in both H3 and D3. Its analysis shows that it is a 2A1′–2E′ transition and that the upper state is identical with the upper state 3s2A1′ of the 6025 Å band previously analysed (I. Dabrowski and G. Herzberg. Can. J. Phys. 58, 1238 (1980)) while the lower state is the upper state 3p2E′ of the 7100 Å band (G. Herzberg and J. K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 4 publications
2
41
0
Order By: Relevance
“…Note incidentally that the same is not true for the quantum defect at the conical intersection: while the frozen-core calculations of Nager & Jungen [8] predicted a value m = 0.346, the determination of Mistrík et al [6] derived from a highly correlated electronic wave function yielded m = 0.406, that is, a significantly increased value corresponding to a lowering of the 3pe pair of states by 700 cm −1 . Similarly, the values for the depth of the JT-induced potential minimum determined by Herzberg et al [12], and more recently by Vervloet & Watson [13], also turn out to be consistent with the various quantum-chemical determinations. Herzberg et al [12] and Vervloet & Watson [13] derived their values from the observed rotational structure of the 3pe manifold of levels combined with the vibrational frequency of the 3pe Rydberg state predicted in the study of King & Morokuma [18].…”
Section: Discussion (A) Jahn-teller Parameterssupporting
confidence: 81%
See 3 more Smart Citations
“…Note incidentally that the same is not true for the quantum defect at the conical intersection: while the frozen-core calculations of Nager & Jungen [8] predicted a value m = 0.346, the determination of Mistrík et al [6] derived from a highly correlated electronic wave function yielded m = 0.406, that is, a significantly increased value corresponding to a lowering of the 3pe pair of states by 700 cm −1 . Similarly, the values for the depth of the JT-induced potential minimum determined by Herzberg et al [12], and more recently by Vervloet & Watson [13], also turn out to be consistent with the various quantum-chemical determinations. Herzberg et al [12] and Vervloet & Watson [13] derived their values from the observed rotational structure of the 3pe manifold of levels combined with the vibrational frequency of the 3pe Rydberg state predicted in the study of King & Morokuma [18].…”
Section: Discussion (A) Jahn-teller Parameterssupporting
confidence: 81%
“…Similarly, the values for the depth of the JT-induced potential minimum determined by Herzberg et al [12], and more recently by Vervloet & Watson [13], also turn out to be consistent with the various quantum-chemical determinations. Herzberg et al [12] and Vervloet & Watson [13] derived their values from the observed rotational structure of the 3pe manifold of levels combined with the vibrational frequency of the 3pe Rydberg state predicted in the study of King & Morokuma [18]. The value 86.1 ± 0.7 cm −1 , which we obtain here for the same state, is in quite good agreement with the values given there, viz.…”
Section: Discussion (A) Jahn-teller Parameterssupporting
confidence: 81%
See 2 more Smart Citations
“…[1,2,3,4] and references therein). Most treatments focused on the E⊗e JT effect and on the rovibronic energy level structures of prototypical molecular systems including H 3 [5,6], Li 3 [7], Na 3 [8], CH 3 O [9,10], cyclopentadienyl [11,12], C 6 H + 6 [13,14,15] and C 5 H + 5 [16,17]. The vibronic coupling of a doubly-degenerate electronic state mediated by nondegenerate vibrational modes, i. e., the E⊗(b 1 ⊕b 2 ) or E⊗b JT effects apparent in molecules with a four-fold symmetry axis, has received less attention, maybe because it is considered to be the simplest [3].…”
Section: Introductionmentioning
confidence: 99%